The Loss of Function of the NODULE INCEPTION-Like PROTEIN 7 Enhances Salt Stress Tolerance in Arabidopsis Seedlings - Le, Quang Tri; Lee, Won Je; Choi, Jun Ho; Nguyen, Dinh Thanh; Truong, Hai An; Lee, Sang-A; Hong, Suk-Whan; Lee, Hojoung (Frontiers in Plant Science, 2022)
Plants acquire nitrogen, an essential macronutrient, from soil as nitrate. Because nitrogen availability is a major determinant of crop productivity, soil is amended with nitrogenous fertilizers. Extensive use of irrigation can lead to the accumulation of salt in soil, which compromises crop productivity. Our characterization of NODULE INCEPTION (NIN)-like PROTEIN 7 (NLP7), a transcription factor regulating the primary response to nitrate, revealed an intersection of salt stress and nitrate metabolism. The growth of loss-of-function mutant nlp7 was tolerant to high salinity that normally reduces the fresh weight and chlorophyll and protein content of wild type (Col-0). On medium with high salinity, nlp7 experienced less stress, accumulating less proline, producing less nitric oxide (NO) and reactive oxygen species and expressing lower transcript levels of marker genes RD29A and COR47 than Col-0. Nevertheless, more sodium ions were translocated to and accumulated in shoots of nlp7 than Col-0. Because nlp7 also expressed less nitrate reductase (NR) activity, nitrate accumulated to abnormally high levels with or without salinity. We attributed the enhanced salt tolerance of nlp7 to the balanced accumulation of nitrate anions and sodium cations. Our results suggest that nitrate metabolism and signaling might be targeted to improve salt tolerance.